Penerapan HEC-HMS Untuk Pendugaan Erosi Dan Sedimentasi Metode Musle Pada Waduk Paselloreng Di Kabupaten Wajo - Ricky Zefri; Dyah Ari Wulandari; Suripin Suripin (Borneo Engineering : Jurnal Teknik Sipil, 2022)
The problem of soil erosion due to surface runoff entering the Paselloreng Reservoir. To study soil erosion, the HEC-HMS model was applied to simulate soil erosion and sediment yield. To estimate the sediment yield from the HEC-HMS model, a rainfall-runoff model is needed. Therefore, before simulating the erosion model, hydrological analysis was carried out and for the soil erodibility factor (K) of 0.212, the length and slope factor (LS) of 3.725, the vegetation cover factor (C) of 0.175 and the land conservation factor (P) of 1.00. From the calculation of the Universal Soil Loss Equation (USLE) method, the erosion rate is 79.25 tons/ha/yr and the sedimentation rate is 4.50 tons/ha/yr. The simulation results of the precipitation-runoff model obtained a peak discharge of 28.30 m3/s. To simulate the erosion and sediment model in HEC-HMS the Modified Universal Soil Loss Equation (MUSLE) equation was selected based on the land cover of the watertight study area. Manual calculation of the MUSLE method obtained a large erosion rate of 99.96 tons/ha/yr and a sedimentation rate of 5.59 tons/ha/yr, while with the HEC-HMS modeling, the total sediment load during 2021 was 89,688.10 tons with a rate value of 89,688.10 tons. erosion of 98.48 tons/ha/year and sedimentation rate of 5.59 tons/ha/year or 0.23 mm/year with the erosion hazard class is Class III (moderate).